2021
DOI: 10.1080/20473869.2021.1967078
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of therapists conducting psychological assessments and video conferencing therapy sessions with people with mild intellectual disabilities during the COVID-19 pandemic

Abstract: Background. Due to the restrictive measures introduced to tackle the COVID-19 pandemic, therapists working with people with mild intellectual disabilities have had to use video conferencing to continue to conduct their psychological assessments and therapy sessions. This qualitative study explored therapists' experiences of using video conferencing during the initial lockdown period in the Netherlands. Method. In total, seven therapists working at a service organisation supporting people with intellectual disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Over the course of the pandemic, support staff were able to explore their preferences towards both remote and in-person support. Although remote support was sometimes experienced as useful, efficient, and effective, which is in line with previous research (e.g., [ 21 , 22 ]), overall, support staff preferred meeting (new) service users in-person, as they felt this gave them a better impression of their wellbeing and living situation. In other specific cases, however, support staff experienced how service users could benefit from remote support.…”
Section: Discussionsupporting
confidence: 82%
“…Over the course of the pandemic, support staff were able to explore their preferences towards both remote and in-person support. Although remote support was sometimes experienced as useful, efficient, and effective, which is in line with previous research (e.g., [ 21 , 22 ]), overall, support staff preferred meeting (new) service users in-person, as they felt this gave them a better impression of their wellbeing and living situation. In other specific cases, however, support staff experienced how service users could benefit from remote support.…”
Section: Discussionsupporting
confidence: 82%
“…The question is whether reinforcers within our control have a greater value than other stimuli that are concurrently available to our clients. For instance, therapists (psychologists, psychomotor therapists, and an art-based therapist) in Oudshoorn et al’s ( 2021 ) study reported that their participants with mild intellectual disabilities were checking smartphones more often in telehealth than during in-person sessions, which negatively affected their level of participation. Practitioners may need to work with the caregivers to facilitate the arrangement of a context in which competing reinforcers or distractors are minimized during sessions.…”
Section: Preference Assessments and Reinforcers—practice Recommendationsmentioning
confidence: 99%
“…Moreover, even when the program incorporates 2D stimuli, if a client uses a small screen such as a tablet or a smartphone, the visibility of 2D stimuli is not guaranteed (e.g., Oudshoorn et al, 2021 ). In such a case, ABA practitioners might need to reduce the number of stimuli to present on the screen at once, which might conflict with certain programs such as a MTS program that uses five items in an array.…”
Section: Program Adaptation—practice Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several research studies indicate that psychological treatment, delivered remotely though video-conference platforms, are both safe and feasible. Furthermore, that they offer greater flexibility, and improve equity of access ( Appleton et al, 2021 ; Broadbear et al, 2021 ; Cantone et al, 2021 ; Cataldo et al, 2021 ; Dharwadkar et al, 2021 ; Oudshoorn et al, 2021 ; Puspitasari et al, 2021 ; Shklarski et al, 2021a , b ; Vera San Juan et al, 2021 ; Milosevic et al, 2022 ). Smith et al (2022) , however, considers that although the evidence-base is promising further interrogation and research is needed to further explore the ethical and moral dimensions of video-conference psychotherapy.…”
Section: Introductionmentioning
confidence: 99%